PENCEGAHAN TEKANAN DARAH TINGGI PADA LANSIA PENDERITA HIPERTENSI DENGAN METODE WALKING EXERCISE - nur isriani Nur Isriani Najamuddin; Lisda Alvita Lisda Alvita; Alya Andriani Alya Andriani (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Hypertension is a condition where a person experiences an increase in blood pressureblood is above normal and chronic. Hypertension in Indonesia is a problem health with the highest prevalence of 25.8%, the prevalence of Province West Sumatra by 22.6%. Data from Mamasa district, there are 19,559 cases of hypertension with details of 6,891 men and 6,891 women (Mamasa Health Office, 2019). Treatment of hypertension is done by pharmacological and non-pharmacological treatment. One of the non-pharmacological treatments for hypertension is physical activity, namely by walking. This research is an Experimental Design with a Control Group Pre-Posttest approach. The study was carried out from April to May 2021. The sampling method was carried out by purposive sampling, totaling 40 people. The sample was divided into 2 groups, namely 20 treatment samples and 20 control samples. Primary data includes data on respondents' initial and final pressure, while secondary data includes general data on respondents. The data were analyzed using the Paired T Test statistical test. These results indicate an average decrease in systolic and diastolic blood pressure in the groups of 13.40 mmHg and 13.60 mmHg, respectively. The results of the Paired T Test with a p value of 0.000 indicate that there is an effect of the walking exercise method on blood pressure in the elderly (aged 55-60 years) with hypertension in Aralle Village, Aralle District, Mamasa Regency. Suggestions from this study are the walking exercise method can be used as an alternative to non-pharmacological treatment to help lower blood pressure.